2009
DOI: 10.1167/9.3.8
|View full text |Cite
|
Sign up to set email alerts
|

Shape distortions and Gestalt grouping inanorthoscopic perception

Abstract: When a figure moves behind a stationary narrow slit, observers often report seeing the figure as a whole, a phenomenon called slit viewing or anorthoscopic perception. Interestingly, in slit viewing, the figure is perceived compressed along the axis of motion. As with other perceptual distortions, it is unclear whether the perceptual space in the vicinity of the slit or the representation of the figure itself undergoes compression. In a psychophysical experiment, we tested these two hypotheses. We found that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
(54 reference statements)
2
9
0
Order By: Relevance
“…Thus, features presented at one retinotopic location are attributed to another one. These non-retinotopic attributions are not errors of the visual system but rather reflect systematic visual processing that maintains the identity of perceptual objects across space and time (Otto et al, 2009) and follows the rules of perceptual grouping (Aydin et al, 2008(Aydin et al, , 2009Öğmen et al, 2006;Otto et al, 2009). Similar non-retinotopic effects have been demonstrated for luminance (Shimozaki et al, 1999), color Watanabe and Nishida, 2007), shape Otto et al, 2006), size (Kawabe, 2008), and the conjunction of features (Cavanagh et al, 2008).…”
Section: Introductionmentioning
confidence: 60%
“…Thus, features presented at one retinotopic location are attributed to another one. These non-retinotopic attributions are not errors of the visual system but rather reflect systematic visual processing that maintains the identity of perceptual objects across space and time (Otto et al, 2009) and follows the rules of perceptual grouping (Aydin et al, 2008(Aydin et al, , 2009Öğmen et al, 2006;Otto et al, 2009). Similar non-retinotopic effects have been demonstrated for luminance (Shimozaki et al, 1999), color Watanabe and Nishida, 2007), shape Otto et al, 2006), size (Kawabe, 2008), and the conjunction of features (Cavanagh et al, 2008).…”
Section: Introductionmentioning
confidence: 60%
“…This proposal has been supported by a recent study where spatial distortions in anorthoscopic perception were examined (Aydin et al, 2008). The figure moving behind the slit typically appears spatially compressed in the direction of its motion (e.g., Anstis & Atkinson, 1967; Aydin et al, 2009; Haber & Nathanson, 1968; Helmholtz, 1867/1962; McCloskey & Watkins, 1978; Morgan et al, 1982; Parks, 1965; Rock, 1981; Rock & Sigman, 1973; Zöllner, 1862). Aydin et al, (2008) showed that this spatial compression can be explained by the differences in the perceived speeds of the leading and trailing parts of the anorthoscopic figure.…”
Section: Discussionmentioning
confidence: 99%
“…A critical observation from these experiments is that, if one does not take into account the direction of motion, then the interpretation of the stimulus will be ambiguous in that mirror-symmetric images moving in opposite directions will generate identical patterns in the slit. Therefore, the direction of motion must be an essential component in building non-retinotopic representations associated with anorthoscopic perception [5],[6],[52],[57]. …”
Section: Insights On Non-retinotopic Representations From Studies mentioning
confidence: 99%
“…While both parts appear to move faster than their veridical speed, the trailing part appears even faster than the leading part in accordance with our hypothesis. Data, replotted from [6], represent the average and the standard error of the mean across the observers.…”
Section: Figmentioning
confidence: 99%